Corporate IT transformation at BARCO. Issue 2 (December 2013) - Viaene, Stijn; Işık, Öykü
The case takes us back to 2009, a year of great turmoil and the start of a transformation journey for BARCO, a global visualisation solutions company. Stefaan Kindekens, newly appointed corporate CIO, is preparing the new IT strategy per request of the board of directors. At the heart of the proposal are the introduction of a new IT operating model and the replacement of the legacy systems landscape. The case allows for discussions about business and IT alignment, IT strategy, and IT governance.